BAHASA INGGRIS - Munasarah; Isna, Nuzulul (ELTIN Journal, 2024)
Vocabulary is the first language component that students should master. However, many students faced problems in mastering vocabulary. This study aims to find out the improvement of students’ vocabulary through the use of Kubis and to investigate the obstacles faced by the students in learning vocabulary by using the Kubis application. This research employed Mix-method. The data was collected using the test and interview.  Seventh-grade students were involved in this study as the respondents of the research. The result of this study showed that students’ vocabulary mastery was improved after learning by using Kubis application. However, the data also revealed that there are some obstacles students faced when using Kubis. The difficulties are caused by several reasons, such as technological barriers, passive students, the restriction on using smartphones by the parents, and the application is less interesting for students.